Analysis of Students' Perceptions about Early Leadership Education - Aliffany Pualam Ariarta; Muhammad Sabri Latif; Ulfaturrahmah Ulfaturrahmah; Jannatul Firdausi Nuzula; Munirul Abidin (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
Forming a good and ideal leader is not done instantly, it needs to be done early. This study aims to examine the importance of leadership education for children, the urgency of implementing such education in children starting early, its proper implementation, and the impact of early leadership education according to the perceptions of postgraduate students of Islamic education management. They are using descriptive qualitative research methods, with the type of case study research located at Postgraduate UIN Maulana Malik Ibrahim Malang. Using data collection techniques in the form of interviews, observation and documentation, and data analysis techniques with steps: 1) Data reduction, 2) Presentation of data, and 3) Conclusion of research data The results of this study show that the application of leadership education from an early age is important for children to become ideal leaders. Leadership education has a positive impact on the character and personality of children. Forming an attitude of responsibility, courage, self-confidence, caring for the surroundings, and training children to be able to find solutions to the problems they face. The steps taken also need to be adjusted to the age, ability, and thinking pattern of the child. The role of the people around him, namely, parents, family, teachers, peers, and the surrounding environment is an important part that supports the success of the leadership education process. The conclusion of this research is to increase our understanding of leadership education from an early age. And also increase knowledge about the steps to form a cadre of cadres of national leaders.